Electrically tunable THz graphene metasurface wave retarders - Park Hyunwoo; Jeong Sodam; Seo Changwon; Park Hyeongi; Oh Donghak; Shim Jae-Eon; Lee Jaeyeong; Ha Taewoo; Kim Hyeon-Don; Baek Soojeong; Min Bumki; Kim Teun-Teun (Nanophotonics)
Anisotropic materials with chirality or birefringence can be used to manipulate the polarization states of electromagnetic waves. However, the comparatively low anisotropy of natural materials hinders the miniaturization of optical components and devices at terahertz frequencies. In this study, we experimentally demonstrate that the relative phase retardation of a THz wave can be electrically controlled by integrating patterned mono- and bilayer graphene onto an otherwise isotropic metasurface. Specifically, we show that a refractive index for one of the orthogonal polarization states can be electrically controlled by modulating graphene’s conductivity, thereby weakening the capacitive coupling between adjacent meta-atoms in an anisotropic manner. With monolayer graphene, phase retardation of 15° to 81° between two orthogonal polarization states can be achieved. Maximum phase retardation of 90° through a metasurface with bilayer graphene suggests its use as a tunable quarter-wave plate. Continuous control from linear- to circular-polarization states may provide a wide range of opportunities for the development of compact THz polarization devices and polarization-sensitive THz technology.